Gambaran Tingkat Pengetahuan dan Sikap terhadap Infeksi Menular Seksual pada Siswa-Siswi di Mas Darul Mursyid - Adila Salwa Siregar; Riydah Ikhsan; Fitriyani Nasution; Indra Gunasti Munthe (Pusat riset dan Inovasi Nasional, 2026)
Sexually transmitted infections (STIs) are a reproductive health problem that is still common among adolescents and can have serious impacts if not handled properly. Low levels of knowledge and unfavorable attitudes towards STIs have the potential to increase risky behavior among students. Objectives. This study aims to determine the level of knowledge and attitudes of students towards sexually transmitted infections at MAS Darul Mursyid. Methods. This study employed a cross-sectional methodology and a quantitative descriptive design. All MAS Darul Mursyid students were included in the study population, and a total sampling procedure was used to pick 149 respondents. A questionnaire with 20 statements about knowledge and 10 statements about attitudes around STIs was used to collect data. The SPSS software was used to analyze the data univariately, and the results were displayed as percentages and frequency distributions. Results and Discussion. According to the findings, 78 respondents (52.3%) had an adequate level of understanding, followed by 63 respondents (42.3%) in the poor category and 8 respondents (5.4%) in the good category. In the meanwhile, most students had a favorable opinion of STI prevention. Conclusion: Even though the majority of respondents expressed support for STI prevention initiatives, additional health education and instruction are still required to give students a more thorough grasp of STI prevention.